Strain Measurement Using Fiber Bragg Granting Sensor for Crack Detection - Vinnarasi, K.; Sundaravadivelu, Dr. S. (International Journal of Advanced Engineering Research and Science, 2020)
In this paper the wavelength shift due to strain is measured by using Fiber Bragg Grating sensors. Structural health monitoring is the emerging field where it involves monitoring of several physical parameters. Strain measurement is one of the most external parameter to be measured in various sensing applications. The conventional strain sensors used to measure strain has many disadvantages in terms of low stability, not immune to Electromagnetic Interference (EMI) and other external factors. The Fiber Bragg Grating Sensors has replaced the sensor like strain gauge in various remote applications. The work is centered on fiber optic Bragg grating (FBG) sensors, to detect strains with the wavelength shift that is observed due to the physical perturbation. This kind of strain analysis can be used to monitor strain in complex structures and in remote applications.